Cardiac Safety of Dual Anti‐HER2 Therapy in the Neoadjuvant Setting for Treatment of HER2‐Positive Breast Cancer. (24th March 2017) - Yu, Anthony F.; Singh, Jasmeet C.; Wang, Rui; Liu, Jennifer E.; Eaton, Anne; Oeffinger, Kevin C.; Steingart, Richard M.; Hudis, Clifford A.; Dang, Chau T.
Abstract : Background: Trastuzumab and pertuzumab are approved for the neoadjuvant treatment of human epidermal growth receptor 2 (HER2)‐positive breast cancer, but cardiac safety data is limited. We report the cardiac safety of dose‐dense doxorubicin and cyclophosphamide (AC) followed by paclitaxel, trastuzumab, and pertuzumab (THP) in the neoadjuvant setting followed by adjuvant trastuzumab‐based therapy. Methods: Fifty‐seven patients treated with neoadjuvant dose‐dense AC‐THP followed by adjuvant trastuzumab‐based therapy between September 1, 2013, and March 1, 2015, were identified. The primary outcome was cardiac event rate, defined by heart failure (New York Heart Association [NYHA] class III/IV) or cardiac death. Patients underwent left ventricular ejection fraction (LVEF) monitoring at baseline, after AC, and serially during 1 year of anti‐HER2 therapy. Results: The median age was 46 years (range 26–68). Two (3.5%) patients developed NYHA class III/IV heart failure 5 and 9 months after initiation of trastuzumab‐based therapy, leading to permanent discontinuation of anti‐HER2 treatment. Seven (12.3%) patients developed a significant LVEF decline (without NYHA class III/IV symptoms). The median LVEF was 65% (range 55%–75%) at baseline and 64% (range 53%–72%) after AC, and decreased to 60% (range 35%–70%), 60% (range 23%–73%), 61% (range 25%–73%), and 58% (range 28%–66%) after 3, 6, 9, and 12 months (± 6 weeks) of trastuzumab‐based therapy. Conclusion: The incidence of NYHA class III/IV heart failure after neoadjuvant AC‐THP (followed by adjuvant trastuzumab‐based therapy) is comparable to rates reported in trials of sequential doxorubicin and trastuzumab. Our findings do not suggest an increased risk of cardiotoxicity from trastuzumab plus pertuzumab following a doxorubicin‐based regimen. Abstract : This article reports the cardiac safety data from a single institutional retrospective cohort study of patients with HER2‐positive breast cancer treated with dose‐dense doxorubicin and cyclophosphamide (AC) followed by paclitaxel with trastuzumab and pertuzumab in the neoadjuvant setting followed by completion of 1 year of adjuvant anti‐HER2 therapy.